INOVASI PEMBELAJARAN DIGITAL: INTEGRASI E-BOOK DAN VIDEO INTERAKTIF UNTUK MENINGKATKAN KETERAMPILAN SENAM LANTAI - Muhammad Fitrah Mubarak; Rudolof Yanto Basna; Hans Januaris Orboi; Yeremias Edowai (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Floor gymnastics, as a branch of sport, requires mastery of advanced techniques. However, conventional teaching methods are considered less effective in helping students of the Sports Coaching Education (PKO) program at Cenderawasih University to master both theoretical and practical aspects. The main obstacles include limited meeting time, lack of interactivity, and low learning motivation. To address these issues, this Community Service (PkM) activity proposes the integration of digital learning media in the form of e-books and interactive videos. The implementation method involves three stages: preparation, training, and evaluation, with the participation of 40 students. The post-test results showed a significant improvement in theoretical mastery (17%) and practical skills (26%), with 94.6% of participants stating that the module was very helpful. These findings align with previous research, which indicates that digital media enhances understanding, motivation, and learning flexibility. In conclusion, the combination of e-books and interactive videos is effective in improving floor gymnastics skills. It is recommended to enrich the content with advanced movements and provide technology training for instructors to ensure program sustainability.